Eliciting general practitioners' salient beliefs towards prescribing: A qualitative study based on the Theory of Planned Behaviour in Greece. (27th January 2013) - Tsiantou, V.; Shea, S.; Martinez, L.; Agius, D.; Basak, O.; Faresjö, T.; Moschandreas, J.; Samoutis, G.; Symvoulakis, E. K.; Lionis, C.
Summary What is known and Objective Prescribing represents an important medical action especially in primary care. However, irrational prescribing is common and has an impact on clinical and economic outcomes. Therefore, there is a growing need to rationalize prescribing. Knowledge of influential factors is crucial for achieving this. The aim of the present study was to identify the behavioural, normative and control beliefs of GPs regarding prescribing in Greece. Methods Focus group sessions were conducted in three geographically defined areas in Greece. GPs working in the private and public sector in primary care settings were invited to participate. Transcripts from focus groups were content analysed using the Theory of Planned Behaviour (TPB) as the theoretical framework. Results and Discussion GPs acknowledged prescribing as the most important method for treating diseases in primary health care, with significant impact on patient's health and quality of life. The expectations of patients and their families were extremely influential during prescribing. Pharmaceutical sales representatives, other GPs and specialists, as well as public health authorities influenced prescribing. GPs admitted that factors such as the income of the patient, the limited time available and special situations such as prescribing through a third person or prescribing following patients' prescription requests for medicines that they have previously purchased over the counter through pharmacies may facilitate or hinder their prescribing decision. What is new and Conclusion This elicitation study shed light into GPs' beliefs regarding prescribing. Factors that are not common in the usual European setting were revealed, such as the influence of the patients' family and special situations during prescribing. Thus, various issues were highlighted that should inform the development of items for inclusion in a forthcoming TPB‐based questionnaire. The results of this study revealed also certain issues that can affect the design of policies aiming at the rationalization of prescribing.